Tanggungjawab Perusahaan Jasa Pengangkutan Dalam Pengiriman Barang(Studi Di Surakarta) - , Sugiantoro; , Prof. Dr. Absori, S.H., M. Hum; , Wardah Yuspin, S.H.,M.Kn.,Ph.D (2017)
In our society, a need for goods located in different region from customer can be met by using goods delivery service. The goods delivery needs agreement about matters relating to specified goods starting from type of goods, risk level, cost of delivery and administrative matter and sanctions associated to failure by either party. The writing will discuss about how such agreement will be made between parties involved in goods delivery and what responsibilities of freight company for goods they deliver are. PT. Pos Indonesia, JNE and Lion Cargo as delivery companies offer services such as goods/packages delivery and document delivery. In their activities, goods/packages delivery involved several parties, namely customer/sender, PT. Pos Indonesia, JNE and Lion Cargo, Freight Company and insurance company. In order to guarantee rights and obligations of the parties, then the parties made a legal relationship realized in an agreement. The agreement was reciprocal in nature in which rights of a party will be an obligation for other party. While, agreements made by a freight company was a standardized reciprocal agreement (content of the agreement is written in a form/receipt). The reciprocal agreement involving several parties was intended to provide legal certainty if unwanted condition had occurred.